THE CORRELATION OF NOCTURIA INCIDENCE AND ANXIETY LEVELS DURING THE COVID-19 PANDEMIC - Maharani, Revina; Daryanto, Besut; Gunawan, Atma (Indonesian Journal of Urology, 2024)
Objective: This study aims to examine the relationship between nocturia and anxiety levels as precipitating factors in related study population. Material & Methods: This study used a survey facilitated via Google Form, using the International Consultation on Incontinence Questionnaire Nocturia, Zung Self-Rating Anxiety Scale, and a Demographic Data Questionnaire to obtain corresponding data. The descriptive-analytic method was applied, and Chi-square statistical analysis was performed. Results: From 270 participants, 240 exhibited normal anxiety levels, 28 demonstrated mild to moderate anxiety levels, and two presented severe anxiety levels. Furthermore, 148 participants reported experiencing nocturia, while 122 participants did not exhibit nocturia. Conclusion: This study showed no correlation between anxiety levels and nocturia in students from the Nutritional Science and Nursing Science Programs at Universitas Brawijaya, batches 2019, 2020, and 2021. Keywords: Anxiety level, nocturia, covid-19.